(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In modern linguistics, special attention is paid to the comparative analysis of languages, which is a natural situation, and the rapid development of the understanding of the cultural uniqueness and similarity of different peoples has a unique effect on the development of linguistic sciences, as well as the fields of anthropological sciences.